2017
DOI: 10.1007/s00024-017-1720-x
|View full text |Cite
|
Sign up to set email alerts
|

Natural Time, Nowcasting and the Physics of Earthquakes: Estimation of Seismic Risk to Global Megacities

Abstract: Natural Time ("NT") refers to the concept of using small earthquake counts, for example of M>3 events, to mark the intervals between large earthquakes, for example M>6 events. The term was first used by (Varotsos et al., 2005) and later by (Holliday et al., 2006) in their studies of earthquakes. As we discuss in this paper, it is particularly useful in describing complex stochastic nonlinear systems characterized by fat-tail statistics rather than Gaussian normal statistics. In this paper we discuss ideas and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

6
2

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 25 publications
3
82
0
Order By: Relevance
“…Moreover, the analysis in natural time of the seismicity subsequent to the SES activity in the area revealed [2] that critical conditions were obeyed early in the morning of 18 October 2018, i.e., almost a week before the strong earthquake occurrence, in agreement with earlier findings [4]. The application [2] of the recent method of nowcasting earthquakes [9][10][11][12][13], which is based on natural time, has revealed that an earthquake potential score of around 80% was observed just before the occurrence of this M w 6.8 earthquake. Here, we focus on the recording [14] of additional SES activities after the occurrence of the latter earthquake in the beginning of January 2019 (see below) that preceded the following two earthquakes in Greece during 2019: First, a M w 5.4 earthquake [15] close to Preveza city in Western Greece on 5 February 2019 and a M w 5.3 earthquake [16] on 30 March 2019 a few tens of km East of Patras SES measuring station (labeled PAT in Figure 1).…”
Section: Introductionsupporting
confidence: 81%
“…Moreover, the analysis in natural time of the seismicity subsequent to the SES activity in the area revealed [2] that critical conditions were obeyed early in the morning of 18 October 2018, i.e., almost a week before the strong earthquake occurrence, in agreement with earlier findings [4]. The application [2] of the recent method of nowcasting earthquakes [9][10][11][12][13], which is based on natural time, has revealed that an earthquake potential score of around 80% was observed just before the occurrence of this M w 6.8 earthquake. Here, we focus on the recording [14] of additional SES activities after the occurrence of the latter earthquake in the beginning of January 2019 (see below) that preceded the following two earthquakes in Greece during 2019: First, a M w 5.4 earthquake [15] close to Preveza city in Western Greece on 5 February 2019 and a M w 5.3 earthquake [16] on 30 March 2019 a few tens of km East of Patras SES measuring station (labeled PAT in Figure 1).…”
Section: Introductionsupporting
confidence: 81%
“…We have shown in companion papers (Rundle et al, 2018) that the nowcasting method is generally not very sensitive to the choice of large spatial region defining the histogram, leading to a standard error of approximately ±10%. However, the method is strongly sensitive to issues of catalog completeness (Rundle et al, 2018).…”
Section: Discussionmentioning
confidence: 95%
“…Nowcasting refers to the use of proxy data to estimate the current dynamical state of a driven complex system such as earthquakes, neural networks, or the financial markets . In previous papers Rundle et al, 2018), a method to nowcast earthquakes has been presented based on RUNDLE ET AL. 191 Earth and Space Science TECHNICAL…”
Section: Nowcastingmentioning
confidence: 99%
“…To better understand the earthquake potential, we compute nowcasts for the area around the Ocotillo site within circles of radius 25 and 100 km (Figure ). Nowcasting is a method for evaluating the current state of the fault system in a seismically active area, which is reset following a moderate to large earthquake (Rundle et al, ; Rundle et al, ). The method uses counts of small earthquakes to evaluate the potential for a large earthquake.…”
Section: Discussionmentioning
confidence: 99%
“…The method uses counts of small earthquakes to evaluate the potential for a large earthquake. Nowcasting is not a prediction, but it can be applied to estimate seismic risk in a region (Rundle et al, ). In the present calculation, which provides a snapshot of the fault system in October 2017, a small earthquake is an event having magnitude 3.99 < = M w < 5, whereas a large earthquake is an event having magnitude M w > 5.…”
Section: Discussionmentioning
confidence: 99%